Biogenic synthesis of lipopolysaccharide facilitated silver nanoparticles (LPS-AgNPs) and its molecular mechanisms against systemic pathogens MRSA and Salmonella typhi, an in-vitro and in-vivo based approach - Deepthi Ramya Ravindran; Suganya Kannan; Vimala Devi Veeranan; Shanmugaiah Vellasamy (Carbohydrate Polymer Technologies and Applications, 2025)
One of the most promising green synthesis strategies involves the use of biological systems, particularly bacteria, to produce nanoparticles. Bacteria possess a diverse array of enzymes and metabolites capable of reducing metal ions into stable nanoparticles. This study presents an innovative approach by utilising a sustainable lipopolysaccharide (LPS) produced by Proteus mirabilis VSMKU0111, which was studied for its genomic traits via whole genome sequencing and was subjected to synthesising silver nanoparticles (LPS-AgNPs). The LPS and LPS-AgNPs were characterised for their morphological, functional, molecular and structural level conformations. The size of the (LPS-AgNPs) ranges from 70- 90 nm with spherical structure, with a mean zeta potential of -28.6 ± 0.4 mV. The antioxidant activity of LPS-AgNPs expressed both DPPH scavenging (IC50 - 3.5 ± 0.2) and FRAP reduction (IC50 – 3.9 ± 0.3) at the concentration of ¼ XMIC (62.5 µg/ml). The anti-biofilm activity of LPS-AgNPs revealed the dissociation of biofilm matrices in MRSA and Salmonella typhi into planktonic cells by disrupting the quorum sensing property at the concentration of ¼ XMIC (62.5 µg/ml). LPS-AgNPs demonstrated a unique ability to induce moderate but targeted oxidative stress, as evidenced by significantly elevated catalase (MRSA: 0.54 ± 0.03 μmol/mg; S. typhi: 0.83 ± 0.03 μmol/mg) and superoxide dismutase (SOD) activity (MRSA: 4.48 ± 0.13 μmol/mg; S. typhi: 3.94 ± 0.10 μmol/mg). Concurrently, phosphofructokinase (PFK) and citrate synthase levels indicated enhanced glycolytic and TCA cycle flux, suggesting an adaptive upregulation of energy metabolism. Lactate dehydrogenase (LDH) activity further revealed a metabolic bifurcation, supporting both aerobic and anaerobic ATP generation. The treatment of LPS-AgNPs in C.elegans reveals the expanded life span in MRSA (82 ± 3 h) and S. typhi (92 ± 2 h) by reducing the pathogens intestinal colonisation. Extracellular ROS generation was decreased with the treatment of LPS-AgNPs at 100 µg/ml, and the elevated level of ROS was noted in MRSA and S. typhi-infected worms. These findings position LPS-AgNPs as a promising antimicrobial strategy, leveraging redox and metabolic stress to impair bacterial survival while potentially mitigating resistance development.